Genetic and QTL mapping in African bermudagrass. Issue 1 (3rd March 2021) - Yu, Shuhao; Fang, Tilin; Dong, Hongxu; Yan, Liuling; Martin, Dennis L.; Moss, Justin Q.; Fontanier, Charles H.; Wu, Yanqi
Abstract: Cynodon transvaalensis Burtt‐Davy is frequently used to cross with C. dactylon Pers. in the creation of F1 hybrid cultivars that are some of the most widely used in the worldwide turf industry. However, molecular resource development in this species is limited. Accordingly, the objectives of this study were to construct a high‐density genetic map, and to identify genomic regions associated with establishment rate. In this study, we constructed the first high‐density linkage map for African bermudagrass using a genotyping by sequencing approach based on 109 S1 progenies. A total of 1, 246 single nucleotide polymorphisms and 32 simple sequence repeat markers were integrated in the linkage map. The total length of nine linkage groups was 882.3 cM, with an average distance of 0.69 cM per interval. Four genomic regions were identified to be associated with sod establishment rate. The results provide important genetic resources towards understanding the genome as well as marker‐assisted selection for improving the establishment rate in bermudagrass breeding. Core Ideas: Developed the first African bermudagrass high‐density linkage map. Identified four genomic regions associated with turf establishment rate in the species.